GAMBARAN PELAKSANAAN SUPERVISI KEPERAWATAN DALAM PERSPEKTIF PERAWAT PELAKSANA DI RUMAH SAKIT PARU dr. ARIO WIRAWAN SALATIGA - Sugiyarto, Edi, Sulastri S.kp., M.Kes, Arum Pratiwi S.Kp ., M.Kes (2016)
The hospital is a health center that consists of various professions form a unity and respect to each other. Supervision is an effort to help the development and upgrading of the supervised so that they can carry out the tasks that have been assigned activities effectively and efficiently. The purpose of this study was to determine the description of the implementation of the supervision of nursing in the perspective of nurses at the Hospital of Lung dr. Ario Wirawan, Salatiga. The research design is descriptive. The population in this study were nurses at the Hospital of Lung dr. Ario Wirawan, Salatiga. The sample used in this study were 105 nurses. The variable in this study is the implementation of nursing supervision in the perspective of nurses. Analysis of data using univariate analysis. The results showed that as many as 4 respondents (3.8%) state supervision performed poorly, 72 respondents (68.8%) state supervision performed quite well and 29 respondents (27.4%) state supervision performed well. It is recommended that supervisors keep supervision appropriate SOPs and job descriptions that already exist in the Lung Hospital dr. Ario Wirawan, Salatiga. Keywords: implementation supervision, supervisors, nurses